SOSIALISASI PENTINGNYA LEGALITAS USAHA UNTUK PENGEMBANGAN UMKM DI DESA BULAKSARI KABUPATEN CILACAP - Kristanto, Eri; Rahman, Kristanti; Hanifah, Rafa (ICON Publisher, 2025)
Business legality is a standard that must be met by business actors so that their businesses can be declared legally valid. Business legality is a form of approval and permission from the government for the implementation of business activities by MSMEs. This community service program, specifically targeting SMEs in Bulaksari Village, Cilacap Regency, aims to enhance MSMEs' understanding of the importance of business legality. The community service team consists of academic staff from the Accounting Program at STIE Muhammadiyah Cilacap. Business legality plays a crucial role in fostering consumer trust and the sustainability of MSMEs. Through basic management and business legality training for MSME operators. Through this outreach program, the initiative broadens the horizons of MSMEs and encourages them to formalize their businesses promptly to avoid future legal risks. This business legalization outreach program is expected to facilitate MSMEs' access to government services and financial institutions, thereby strengthening the MSME business ecosystem in Cilacap Regency for the better in the future.